Improving The Effectiveness of Research and Community Service Management System - Muh. Sholeh; Anggyi Trisnawan Putra; Martanto Setyo Husodo (Universitas Negeri Semarang, 2024)
In recent years, technological developments and paradigm shifts in the world of education and research demand a transformation in the management system of research and community service. The Institute for Research and Community Service (LPPM) of Universitas Negeri Semarang (UNNES) in its role of realising the responsibility of the Tri Dharma of Higher Education, has made a breakthrough in the field of research and community service through an application called SIPP (Research and Community Service Management Information System) which can be accessed on the website. However, there are still five obstacles that need to be improved. This research intends to identify concrete problems faced by Universitas Negeri Semarang in this regard, and design solutions that can increase the effectiveness of the research and community service management system. The results showed that the development of an Artificial Intelligence (AI)-based Recommendation System has become one of the most effective strategies in enhancing user experience in improving the effectiveness of the research and community service management system at Semarang State University. By utilising AI technology, the SIPP application can optimise the data management process, identify research trends, and facilitate collaboration between researchers.